Prioritization of preventive measures by using the FMEA tool in risk analysis in civil construction - Zaupa, Juliana Caroline Teixeira; Catai, Rodrigo Eduardo; Corrêa, Janine Nicolosi; Zaupa, Julio Cesar (Brazilian Journal of Production Engineering, 2023)
According to Social Security statistics for 2021, the number of accidents at work in Brazil remains high, with 34,000 belonging to the construction sector this year. In this scenario, risk management has high importance in risk analysis for accident prevention. Focusing on this issue, this research was carried out in the civil construction sector between the years 2021 and 2022, with the general objective of prioritizing preventive measures related to work safety in civil construction, verified by the use of the Failure Modes and Effects Analysis (FMEA) tool. In order to obtain data, observational and photographic records were made in the work analyzed in relation to the risks to which workers are exposed. Subsequently, the risk priority analysis was carried out using the FMEA tool. Among the high-Risk Priority Numbers (RPNs) there is the non-use of personal protective equipment, a serious situation due to its high risk. Thus, it can be concluded that the FMEA method contributed to the prioritization of preventive measures related to work safety for the analyzed civil construction work.